Pengaruh Sikap, Kontrol Perilaku dan Religiusitas terhadap Niat Melakukan Whistleblowing - Cindy Rayhan Salsabilla; Erinos NR (Jurnal Eksplorasi Akuntansi, 2023)
The purpose of this research is to determine the influence of attitudes, behavior control and religiosity towards the whistleblowing intentions. This research using purposive sampling method with the respondents working at the Local Government Organization in Bukittinggi City. Respondent consists of 121 people, who served as a head of finance, treasurer expenditures, finance staff, budget makers, commitment making officers, Paying Order Signing Officers, Budget User Authorizations. The data collection technique used in this research is field research in the form of researchers distributing structured questionnaires to 26 Local Government Organizations in Bukittinggi City. This data was analyzed by using multiple regression analysis in SPSS. From the results of data processing, it can be seen that the first variable is the attitude of influence on the intention of whistleblowing with a calculated value of t count> t table that is 7.198> 1.661 it can be said that the first hypothesis received. The results of testing the second variable, namely behavioral control has no affection the intention to do whistleblowing with t count < t table ie -0.359 < 1.661 . The religiosity variable is known that as a positive effect with t count> t table that is 1.967> 1.661 So it can be said that third hypothesis accepted.